Simulasi Distribusi Termal Las Gesek Rotari Pada Penyambungan Mild Steel Berbasis Abaqus - Andika Saputra; Yohanes Yohanes; Ridwan Abdurrahman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The friction welding process occurs as a result of the direct conversion of mechanical energy in the form of friction into thermal energy. Thermal in the region near the peak joint has a significant effect on the formation of flash, the hot zone and the strength of the rotary friction welded joint. In this study, observations were made on the validation of the thermal distribution with the welding time reaching flash in experimental testing using a thermocouple sensor measuring instrument and the simulation using ABAQUS software. The test results will be carried out with a tensile test to see the maximum tensile strength of the variation of the chamfer angle 0 °, 15 °, 30 °, 45 °. The conclusions obtained are: (1) The form of thermal distribution from experimental and simulation testing is considered to be in accordance with the percentage error of the maximum thermal value of 37.55%. This is influenced by the slow thermal propagation on the friction surface. (2) Requirement of thermal distribution time in simulation and experimental testing, the shortest time is 59 seconds and 71 seconds at 0 ° chamfer angle and the longest time at 45 ° chamfer angle with 600 seconds and 494 seconds for simulation and experimental testing. This is influenced by the friction surface area and the small heat flux value. (3) The maximum tensile test results were obtained at a 45 ° chamfer angle of 505.53 MPa. Keywords: Rotary Friction Welding, Thermal Distribution, Abaqus